Short communication: First report of black queen-cell virus detection in honey bees (Apis mellifera) in Spain - Higes, M.=700 1 Esperon F.; Sanchez Vizcaino, J.M.
(En, Es)
Ilus., 18 ref.
Keywords: APIS MELLIFERA; ENFERMEDADES INFECCIOSAS; LESION; MORTALIDAD; COLONIA DE ABEJAS; NOSEMA APIS; ESPAÑA